PRENATAL TORSION OF TESTIS: A RARE EMERGENCY - Neha Singh Shrivastava; Chandrasekhar Gopalaswamy; Ram Mohan Chivukula Venugopal (EL-Med-Pub, 2012)
Prenatal torsion of testis is an extremely rare surgical emergency with controversial management guidelines. Controversy exists not only with regard to timing and necessity of exploration but also whether or not to fix the contralateral testis as there is no predisposing anatomical defect. Though not life-threatening, it risks fertility of an otherwise healthy newborn male if overlooked. We describe a case of prenatal testicular torsion and discuss pertinent issues.